Prevention of HIV/AIDS Transmission in Key Communities in Surabaya - Abdul Kohar Mudazkir; Yenny Puspitasari (Universitas STRADA Indonesia, 2024)
Indonesia is in third place among Asia Pacific countries for the growth and spread of HIV with a total of 46,000 cases. East Java Province is designated as an area with concentrated HIV prevalence along with five other provinces, namely DKI Jakarta, Papua, Bali, Riau and West Java. Knowledge is one of the predisposing factors in early detection of HIV disease, as well as risky behavior that can cause HIV AIDS transmission. This research aims to provide education to key communities as an effort to increase knowledge about HIV AIDS prevention and transmission. This research takes the form of experimental research, namely by measuring the increase in respondents' knowledge through pretest and posttest after the intervention. The intervention takes the form of providing education related to knowledge of preventing HIV/AIDS transmission. The intervention that will be carried out to increase knowledge about safe sexual behavior and preventing HIV AIDS transmission will be carried out by providing education on preventing HIV AIDS transmission in key communities at the Mahameru Foundation for 40 respondents. Risky sexual behavior such as having sexual relations with irregular partners, not using condoms during sexual intercourse, having sexual relations under the influence of alcohol and drugs are still carried out by key communities. The level of knowledge regarding risky sexual behavior, how HIV AIDS is transmitted and how to prevent HIV AIDS before education is carried out is still low.